ANALISIS MOTIVASI BELAJAR (EKSTRINSIK) SISWA PENGGUNA FACEBOOK PADA SMAN 3 PUJUD - Tarmini '; Raja Arlizon Raja Arlizon; Sardi Yusuf Sardi Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract ; This study, entitled "Analysis of Learning Motivation (Extrinsic) Students at SMAN 3 Facebook Users Pujud". (Tarmini:1205188157͗) The purpose of this is: 1) to describe the learning motivation (extrinsic) students at SMAN 3 facebook users Pujud. 2) to determine the level of learning motivation (extrinsic) facebook user students at SMAN 3 Pujud each indicator. The method used in this research is descriptive method. The findings of this study are: 1) an overview of learning motivation (extrinsic) facebook user students at SMAN 3 Pujud, the average extrinsic motivation in middle category, 2) the level of learning motivation (extrinsic) facebook user students at SMAN 3 Pujud, based on the intensity of motivation learning (extrinsic) is the most dominant learn in order to obtain the prize. Based on the findings of this study, it can be recommended the following things: 1) it is recommended that the teacher in teaching and learning to pay attention to the problems being faced by the students, especially in terms of providing motivation to students, 2) For parents for more attention to their interests and talents and handaknya parents always encourage children to continue to have a high learning motivation, 3) For students, especially those with extrinsic motivation are classified into categories in order to further enhance low extrinsic motivation by: (a ) diligently face the task, (b) ductile face of adversity, (c) more than happy to work independently, (d) happy to locate and troubleshoot problems, 4) In order to do further research on the results of this study, which is about the causes of learning motivation (extrinsic) dominant found in the student facebook users in SMAN 3 Pujud. Keywords: learning,motivation